Minimalisasi Jumlah Tiang dalam Group Pile Melalui Pemilihan Bentuk Dasar Penampang Pondasi Tiang pada Tanah Lempung - Isnaniati, Isnaniati; Riduwan, Riduwan (Jurnal Semesta Teknika, 2014)
Having very small coefficient of seepage, wide clog, , soil bearing capacity is very low., create the complexity of clay. The pole foundation is what frequently used in clay. Mostly the hard layer of clay soil is far lying under ground along with the rare use of hexagonal foundation which had widely been circular and rectangular. Minimizing the pole in pile group is one of the alternatives to reduce the construction budget. By comparing the pole circle-basis, rectangular, and hexagonal section with variation of dimension 0.3; 0.35; 0.4m, an investigation to the number of pole in pile group based on SPT for vertical soil bearing capacity as well as lateral Brooms method at each cross-sectional shape of the pole is carried out. The results obtained shows similar diameter which finds the number of poles at least up to the highest, in the pile group is a consecutive sequence of rectangular cross-sectional shape of the first, second is a circle, and the third is a hexagon. The percentage of number of rectangular poleÂ Â  78% from circular and 73% from hexagonal shape.